Psychological and Pedagogical Features of Professional Activity in Educational Institutions in the Context of National- Patriotic Education - Boichuk, Vitaliy; Boіchuk Oksana; Moroz, Ruslan (Theoretical and Methodical Problems of Children and Youth Education, 2025)
The search for ways to develop edu cation in the context of russia’ s war against Ukraine deepens the understanding of the need for the united, powerful, and qualified action by the state authorities and administration at all levels. The article analyzes the pressing issue of national patrio tic education in the Ukrainian education system in the current context . The authors focused on the psychological and pedagogical features of professional activity in educational institutions in the context of national patriotic education . They investigated the peculiarities of educational activities in security oriented lyceums and national patriotic education. Given the specifics of the lyceum's educational activities, a special place in it is occupied by the educational direction, namely: measures to form a nationally conscious, patriotic personality in lyceum students, their professional self determination, and their readiness to defend humanistic values, the integrity, independence, and sovereignty of Ukraine. For this purpose, it is necessary to organiz e information and educational events, excursions, meetings, and master classes, and to participate in art festivals and involve students in volunteer and charitable activities. It was established that educational work with children whose parents participa ted or are participating in the events to ensure national security and defense, repel and deter russia’ s armed aggression against Ukraine requires constant psychological support. The content of academic subjects in the context of national patriotic educati on must be carefully selected to form an individual in accordance with the tasks defined in the “Concept of National Patriotic Education in the Education System of Ukraine” Ukraine”. The constant study of the specifics of the work of the units of the Ministry of In ternal Affairs of Ukraine occupies a special place in the education of lyceum students. Professional pedagogical activity in specialized educational institutions involves a specific work schedule, the selection of content for academic subjects, special at tention to the educational aspect of educational activities, and requires special psychological support.